2018
DOI: 10.3892/or.2018.6861
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‑transferase isozyme alpha 1 is predominantly involved in the cisplatin resistance of common types of solid cancer

Abstract: The roles of glutathione S-transferase pi 1 (GSTP1), glutathione S-transferase mu 2 (GSTM2) and glutathione S-transferase alpha 1 (GSTA1) in cisplatin (DDP)-resistance of solid cancer cells (A549/DDP, SKOV3/DDP and SGC7901/DDP) were compared following expression downregulation with small interfering RNAs (siRNAs). DDP cytotoxicity was reflected by its half maximal inhibition concentration (IC 50 ) calculated from data using a Cell Counting Kit-8 assay; cell apoptosis was examined using flow cytometry and Hoech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Thus, the proposition that the role of GST P1-1 in cis -DDP inactivation is due to enzymatic conjugation of GSH with cis- DDP is not supported (14, 44, 45), but the GST P1-1–induced resistance to cis -DDP–induced cell death is instead mediated by one of its other functions (40). Note that it has also been suggested that the isoenzyme alpha 1 (GST A1-1) is also involved in cis -DDP resistance, but the biochemical mechanism underlying GST A1-1–mediated cis -DDP resistance has not been clarified (46).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proposition that the role of GST P1-1 in cis -DDP inactivation is due to enzymatic conjugation of GSH with cis- DDP is not supported (14, 44, 45), but the GST P1-1–induced resistance to cis -DDP–induced cell death is instead mediated by one of its other functions (40). Note that it has also been suggested that the isoenzyme alpha 1 (GST A1-1) is also involved in cis -DDP resistance, but the biochemical mechanism underlying GST A1-1–mediated cis -DDP resistance has not been clarified (46).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning MOC-2, the group of enzymes glutathione S-transferases (GSTs) can play a role in cisplatin chemoresistance, since a higher conjugation of platinum derivatives with glutathione produces more inactive metabolites and a reduction of intracellular concentrations of active drugs [23]. Higher activity of GST alpha 1 (GST1A) has been associated with the resistance to cisplatin in several solid tumors [36], however, low expression of GST1A was found in HB specimens [29]. Upregulation of GSTmu (GSTM) was observed in two thirds of HB xenografts after treatment with cisplatin [37].…”
Section: Mechanisms Of Hb Resistance To Platinum Derivativesmentioning
confidence: 99%
“…GSTA1 is known to inactivate alkylating drugs such as Busulfran, Brostallicin, Carboplatin, cyclophosphamides and anthracycline drugs such as doxorubucin etc. through glutathione conjugation [32,33]. In addition to its catalytic activity, GSTA is also involved in preventing JNK1 induced apoptosis in cases of oxidative stress and cytokine mediated inflammatory response.…”
Section: Discussionmentioning
confidence: 99%